Ketogenic diet to manage refractory epilepsy in the cdkl5 disorder - Lim, Z.; Downs, Jennepher; Wong, K.; Leonard, H. (BMJ Publishing Group, 2017)
Objectives: Mutations involving the CDKL5 gene have been identified as a cause of severe epileptic encephalopathy, often later presenting with features similar to Rett syndrome.1 Cardinal features of epilepsy in the CDKL5 disorder include early onset at a median age of six weeks and poor response to anti-epileptic drugs (AEDs).2 The Ketogenic Diet (KD) was first introduced in the 1920s and is as a second- or third-line intervention for paediatric refractory epilepsy.3 This study investigated the use of KD in the CDKL5 disorder and its influences on seizures. Methods: The International CDKL5 Disorder Database (ICDD), established in 2012, collects information from caregivers and clinicians of individuals with the CDKL5 disorder. Families provided information regarding seizure characteristics, use of and side effects of the KD treatment. Descriptive statistics and time to event analyses were performed. Results: Data regarding KD use was available for 204 individuals with a pathogenic CDKL5 mutation. Median age of ascertainment to the database was 4.8 years (range 0.3–33.9 years) with median age of seizure onset of 6 weeks (range 1 day–65 weeks). History of KD use was reported for 51% (104/204) which was used for a median duration of 17 months (95% CI 9 to 24). Changes in seizure activity after commencing KD were reported for two-thirds of individuals (69/104), with positive effects reported for 88%. Nearly one-third (31.7%) experienced side effects during the diet. At ascertainment, only one-third (32%) remained on the diet with lack of long-term efficacy as the main reason for diet discontinuation (51%, 36/70). Conclusions: Benefits of KD in the CDKL5 disorder coincide with findings of previous trials on refractory epilepsy. However, poor long-term efficacy remains as a significant barrier. In view of its side effects, KD should be commenced under the guidance of a paediatric neurologist and/or specialist dietitian.